Concentrations of vitamins A and E in amniotic fluid, extraembryonic coelomic fluid, and maternal serum in the first trimester of pregnancy. Issue 1 (July 1994) - Campbell, J; Wathen, N C; Merryweather, I; Abbott, R; Muller, D; Chard, T
Abstract : Paired samples of amniotic fluid and coelomic fluid were obtained by transvaginal ultrasound guided amniocentesis from 15 women with an ultrasonographically normal pregnancy between 8 and 12 weeks' gestation. Vitamins A and E were measured in the two pregnancy fluids and in maternal serum by high performance liquid chromatography with detection by ultraviolet absorption and fluorimetry respectively. Concentrations of vitamins A and E were higher in maternal serum than in coelomic fluid and were generally undetectable in amniotic fluid. All differences in concentration were significant. The vitamin E/cholesterol ratio was similar in maternal serum and coelomic fluid. No correlation was shown between the vitamin concentrations in the three fluids. These findings suggest that the coelomic cavity plays a part in the maternofetal exchange of these vitamins.